Task shifting for non-communicable disease management in low and middle income countries--a systematic review. - Rohina Joshi; Mohammed Alim; Andre Pascal Kengne; Stephen Jan; Pallab K Maulik; David Peiris; Anushka A Patel (PLoS ONE)
Background One potential solution to limited healthcare access in low and middle income countries (LMIC) is task-shifting- the training of non-physician healthcare workers (NPHWs) to perform tasks traditionally undertaken by physicians. The aim of this paper is to conduct a systematic review of studies involving task-shifting for the management of non-communicable disease (NCD) in LMIC. Methods A search strategy with the following terms "task-shifting", "non-physician healthcare workers", "community healthcare worker", "hypertension", "diabetes", "cardiovascular disease", "mental health", "depression", "chronic obstructive pulmonary disease", "respiratory disease", "cancer" was conducted using Medline via Pubmed and the Cochrane library. Two reviewers independently reviewed the databases and extracted the data. Findings Our search generated 7176 articles of which 22 were included in the review. Seven studies were randomised controlled trials and 15 were observational studies. Tasks performed by NPHWs included screening for NCDs and providing primary health care. The majority of studies showed improved health outcomes when compared with usual healthcare, including reductions in blood pressure, increased uptake of medications and lower depression scores. Factors such as training of NPHWs, provision of algorithms and protocols for screening, treatment and drug titration were the main enablers of the task-shifting intervention. The main barriers identified were restrictions on prescribing medications and availability of medicines. Only two studies described cost-effective analyses, both of which demonstrated that task-shifting was cost-effective. Conclusions Task-shifting from physicians to NPHWs, if accompanied by health system re-structuring is a potentially effective and affordable strategy for improving access to healthcare for NCDs. Since the majority of study designs reviewed were of inadequate quality, future research methods should include robust evaluations of such strategies.